Coccolithophore abundance and production and their impacts on particulate inorganic carbon cycling in the western North Pacific - Y. Han; Y. Han; Z. Steiner; Z. Cao; D. Fan; J. Chen; J. Yu; M. Dai (Biogeosciences)
Coccolithophores are globally distributed, calcifying phytoplankton that play an important role in the marine carbon cycle through their contribution to the carbonate pump. However, limited knowledge of their biogeography and environmental drivers hinders our ability to predict the response of the marine carbonate pump to climate change. Here, we investigated coccolithophore abundance, species composition, coccolithophore-derived calcium carbonate (CaCO3 as calcite), and particulate inorganic carbon (PIC) concentrations in the upper water column of the western North Pacific Ocean. Sampling was conducted along a meridional transect spanning the oligotrophic subtropical gyre and the nutrient-rich Kuroshio–Oyashio transition region. Our results show that Umbellosphaera tenuis is the numerically dominant coccolithophore species in the subtropical gyre, while Emiliania huxleyi and Syracosphaera spp. dominated in the transition region. The coccolithophore community composition exhibited significant depth- and latitude-dependent variations. On average, coccolithophore calcite contributed 79 ± 27 % of the total CaCO3  standing stock in Niskin bottle samples from the euphotic zone, with a higher contribution observed in the subtropical gyre (91 ± 30 %) compared to the Kuroshio–Oyashio transition region (70 ± 24 %). This pattern was further supported by size-fractionated PIC data from in situ pump samples, with the small size fraction (1–51 µm) contributing 76 ± 11 % of the total PIC (> 1 µm) in the subtropical gyre, compared to 67 ± 13 % in the transition region. During the sampling period, coccolithophore CaCO3 production rates ranged from 0.8 to 2.1 mmol m−2 d−1, averaging 1.5 ± 0.7 mmol m−2 d−1 in the subtropical gyre and 1.2 ± 0.4 mmol m−2 d−1 in the transition region. These findings highlight the critical role of coccolithophores in the pelagic CaCO3 cycle, particularly in oligotrophic ocean waters, and emphasize the need for improved mechanistic understanding of their distribution and calcification dynamics in a changing ocean.